Minority Talent Loss and the Texas Top 10% Law - Niu, Sunny Xinchun (2008)
OBJECTIVE: To examine how knowledge about the Texas top 10% law influences college enrollment decisions of high achieving students minority and nonminority students. DATA AND METHODS: Using a representative survey of graduates from Texas public high schools in 2002, we compare self-reported and transcript-verified class rank and estimate probit models to assess the likelihood that top-ranked minority students know about the law. RESULTS: Family socioeconomic status largely explains why highly ranked black and Hispanic students know less about the top 10% law than comparable whites, but parents’ lack of fluency in English is a significant information barrier for college-bound, top 10% Hispanic students from predominantly minority high schools. Nearly one-fifth of college-oriented black and Hispanic top 10% seniors who did not know about the law failed to enroll anywhere. CONCLUSION: Inadequate information about the top 10% law undermines enrollment of talented minorities in higher education.